A qualitative meta-synthesis examining spirituality as experienced by individuals living with terminal cancer. Issue 2 (18th August 2022) - Hayden, Lucy; Byrne, Emma; Deegan, Avril; Dunne, Simon; Gallagher, Pamela
This review aimed to examine and synthesise literature on spirituality as experienced by individuals living with terminal cancer. Six databases were systematically searched for studies with qualitative findings relevant to spirituality and terminal cancer. Thirty-seven studies were included and thematic synthesis was used to identify themes. Analytical themes included: making sense of dying; living with dying; feeling connected; and being reflective. This review highlights how the experience of spirituality can positively impact the lives of terminal cancer patients. Further, these findings suggest that spirituality can be a transformative experience that allows individuals to experience peace at end of life.